The Meaning of Grief in the Song Lyrics of "Paint It Black" by The Rolling Stones - Maulana, Muhamad Trian; Suswanto, Deni; Sakinah, R. Myrna Nur (Journal of Authentic Research, 2026)
Song lyrics serve as a medium for expressing complex emotions, including grief and loss. This study aims to analyse the representation of grief in "Paint It Black" by The Rolling Stones using Ferdinand de Saussure's semiotic theory and Elisabeth Kübler-Ross's Five Stages of Grief model. The data consist of 9 stanzas of the song's lyrics that were analysed using a qualitative descriptive method, examining the lyrics by identifying signifiers and signifieds and interpreting their meanings through the process of signification. The findings reveal that grief is represented through recurring symbols such as black cars, funeral flowers, darkness, and color imagery, which signify mourning, emotional suffering, hopelessness, and irreversible loss. The analysis identifies four stages of grief, denial, anger, bargaining, and depression, with depression emerging as the dominant stage. This research contributes to semiotic and literary studies by demonstrating how Saussurean semiotics can be integrated with psychological grief models to analyse emotional expression in song lyrics. The study concludes that "Paint It Black" portrays grief as a transformative experience communicated through a rich system of symbolic signs.